Speaking Tasks On Students' English Textbook “Teacher’s Book For Elementary Schools" For 5th Grade. - Yulianda, Wike; Riza, Armilia; Ikhsan, Khairi (JUPE : Jurnal Pendidikan Mandala, 2023)
Abstract. The purpose of this study is to find and analyze all types of speaking tasks found in the English textbook. "Teacher's book for elementary schools for 5th Grade". The data source is an English textbook titled "Teacher's Book for elementary schools for 5th Grade". The researchers only examined speaking tasks in semester 1 which consists of 5 chapters and all of them have speaking tasks. The total speaking task found was 10 speaking tasks. In this study, the researcher used document analysis. According to Simonova, there are seven types of speaking tasks, namely; Dialogue, Role plays, Information gap, Using a picture, Giving instruction, Problem-solving, and Re-telling story. Based on the analysis done by the researcher, there are three types of speaking tasks found in the English textbook entitled "Teacher's book for elementary schools for 5th Grade", namely; Role plays, Using pictures, and Giving instruction. Due to the lack of speaking tasks found in the "Teacher's Book for elementary schools for 5th Grade", it can be said that the types of speaking tasks in the "Teacher's Book for elementary schools for 5th Grade" are still not varied. Using Picture is a task that asks students to tell a picture to communication or describe.